Histone Lactylation Participates in Psoriasis Progression by Regulating the Adiponectin Expression - Zhao S; Wu T; Fu M; Zhang Z (Dove Medical Press, 2024)
Sicheng Zhao, Tingyan Wu, Mingjing Fu, Zhe Zhang Department of Dermatology, Suzhou Kowloon Hospital, Shanghai Jiao Tong University School of Medicine, Suzhou, People's Republic of ChinaCorrespondence: Sicheng Zhao, Department of Dermatology, Suzhou Kowloon Hospital, Shanghai Jiao Tong University School of Medicine, No. 118 Wansheng Street, Suzhou Industrial Park, Suzhou, Jiangsu, 215028, People's Republic of China, Email zscba@163.comBackground: Psoriasis is a chronic inflammatory skin disease characterized by erythema, papules, and plaques. Adiponectin (ADIPOQ) is an important protein hormone secreted by adipose tissue. Here, we aimed to explore the expression of ADIPOQ in psoriasis patients and the moderation effect of histone lactylation on ADIPOQ.Methods: The GSE78097 data set was downloaded from GEO database to analyze the differentially expressed genes (DEGs) in psoriasis. A total of 36 psoriasis patients were recruited to obtain the skin samples. The ADIPOQ protein levels, global lactylation and histone lactylation (H3K18lac) levels were detected by Western blot assay. Chromatin immunoprecipitation (CHIP) assay was performed to detect the combination between H3K18lac and promoter regions of the ADIPOQ. The receiver operating curve (ROC) analysis was used to evaluate the diagnostic value of ADIPOQ in psoriasis.Results: ADIPOQ was decreased in the skin tissues of psoriasis patients. In addition, the global lactylation and H3K18lac levels were significantly decreased in the skin tissues of psoriasis patients. In HaCaT cells, promoting the global lactylation and H3K18lac levels increased the ADIPOQ protein levels, while si-LDHA transfection decreased the ADIPOQ protein levels. The CHIP results indicated that lactylation promoted the binding of promoter regions of the ADIPOQ and H3K18lac. Finally, the ROC analysis showed that ADIPOQ exhibited diagnostic value in psoriasis.Conclusion: This study demonstrated ADIPOQ was decreased in the skin tissues of psoriasis patients, and ADIPOQ has diagnostic value for psoriasis. Furthermore, down-regulation of H3K18lac levels inhibited the transcription of ADIPOQ, which was the key factor of decrease of ADIPOQ levels in psoriasis patients.Keywords: psoriasis, ADIPOQ, histone, lactylation